Kelompok Usaha Serundeng Kepah di Pusat Pemasaran dan Food Court Makanan Khas Tanjungbalai - Hodriani Hodriani; Nurmala Berutu; Ana Rahmi; Zulkarnain Siregar; Wiflihani Wiflihani; Anggreni Atmei Lubis; Agung Suharyanto (Universitas Medan Area, 2022)
This Community Partnership Program (PKM) generally aims to assist Business Groups in making Serundeng Kepah as a typical Tanjungbalai dish in making this product utilizing marine food or natural resources in Tanjungbalai City. Partners in this PKM are Business Groups in Pantai Burung Village, South Tanjungbalai District, Tanjungbalai City. The problem faced by partner members is the lack of knowledge in managing and utilizing existing natural resources as a product of the Tanjungbalai food development business. The method used to achieve the objectives of this service activity is the method of education, socialization, assistance in product manufacture, and business management on products that have been produced. The results of the activities, an increase in the quality of human resources in knowledge in the management and utilization of local natural resources and business management; Serundeng Kepah Products as Tanjungbalai Specialty Food; and Logo Making, Packaging design and product IPR.